Individual and Environmental Dimensions in Entrepreneurial Intention of University Students - Sousa, Antonia Márcia Rodrigues; Fontenele, Raimundo Eduardo Silveira; Santos, Ruan Carlos dos (Journal of Sustainable Competitive Intelligence, 2023)
Purpose: This article proposes to measure the influence of individual and environmental factors on the entrepreneurial intention of university students in the creation of companies. Methodology/approach: It is a quantitative study. The factorial analysis, using the Varimax rotation method, was used to know the factorial load of 43 variables, including the characterization of the respondents, with a sample of 540 cases, collected through a questionnaire with students of the last year of the course administration in the five most populous capitals of Brazil. Then, logistic regression analysis was used, making it possible to know the significant correlation of independent variables with the dependent variable. Originality/Relevance: They show a greater influence of the individual factors represented by the entrepreneurial motivation and entrepreneurial self-efficacy in the intention to create companies and presents discussions regarding the individual and environmental factors that determine or guide the entrepreneurial intention of university students. Key findings: It is possible to consider that although the chosen sample resembles the profile of new entrepreneurs, it cannot be guaranteed that it is the best representation of this category. Theoretical/methodological contributions: The study opens new discussions regarding the individual and environmental factors that determine or guide the entrepreneurial intention of university students, enabling the organizations that promote the teaching of entrepreneurship to create new teaching methodologies, directed to the formation of potential entrepreneurs.